2009
DOI: 10.1021/bi9001387
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Dependent Conformational Changes in Cytochrome c Oxidase Suggest a Gating Mechanism for Proton Uptake

Abstract: A role for conformational change in the coupling mechanism of cytochrome c oxidase is the subject of controversy. Relatively small conformational changes have been reported in comparisons of reduced and oxidized crystal structures of bovine oxidase, but none in bacterial oxidases. Comparing the x-ray crystal structures of the reduced (at 2.15 Å resolution) and oxidized forms of cytochrome c oxidase from Rhodobacter sphaeroides, we observe a displacement of heme a 3 involving both the porphyrin ring and the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
197
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(210 citation statements)
references
References 62 publications
13
197
0
Order By: Relevance
“…The reduction procedure for the crystals was performed in stabilizing solution with 10 mM sodium dithionite at 4°C as previously described (3). After a few minutes of dithionite soaking, the crystals turned green, indicating the reduction of the crystals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction procedure for the crystals was performed in stabilizing solution with 10 mM sodium dithionite at 4°C as previously described (3). After a few minutes of dithionite soaking, the crystals turned green, indicating the reduction of the crystals.…”
Section: Methodsmentioning
confidence: 99%
“…Spectra of the I-II RsCcO frozen crystals were recorded at 100 K using the online singlecrystal microspectrophotometer in station 14-BM-C, BioCARS, Advanced Photon Source, Argonne National Laboratory (3,35). Annealing was performed on the crystals after X-ray radiation, during which the cooling nitrogen flow was blocked for 3-4 s to allow temperature increase of the crystals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive study on the proton pumping mechanism in A-type bovine aa 3 COX by Yoshikawa and coworkers indicates the several structural changes around the heme active site and putative proton pumping pathway upon the reduction of the heme and/or the binding of the ligand to the heme (42). Similarly, Ferguson-Miller and co-workers observed the redox change-and/ or ligand binding-induced structural changes in aa 3 COX from Rhodobacter sphaeroides (39). As a transduction pathway for the structural changes, recent time-resolved spectroscopic study on bovine aa 3 COX suggested that the vinyl group of heme a 3 could be involved (48).…”
Section: Figmentioning
confidence: 92%
“…The mechanism of proton transfer and pumping was most extensively studied in A-type COXs. A-type COXs have at least two proton transfer pathways called K-and D-pathways from the inside of the cellular membrane to the active center (39,42). Some protons are used for the catalytic O 2 reduction at the active center, and the other protons are further transferred to the outside of the membrane through proton pumping pathway(s) which is not clearly identified yet.…”
Section: Proton Transfer From Outside Versus Inside Of Cellular Membranementioning
confidence: 99%